Findings from the Caring International Research Collaborative: Using Caring Science To Assess and Support Food Sustainability Systems for Women Living with HIV/AIDS in a Village in Cameroon - Relindis Oyebog Moffor; Jared Nelson; Molly Jahn; John Nelson (Interdisciplinary Journal of Partnership Studies, 2015)
This study proposes Caring Science as an innovative way to facilitate food systems sustainability in areas of the world that continue to suffer from food insecurity and food shortages. An interdisciplinary group that included a nurse, an agronomist, an environmentalist, and a statistical analyst collaborated to study food sustainability in a village in Bambui, Cameroon. The village was composed of only women and children, and all the women were diagnosed with HIV/AIDS. This interdisciplinary approach not only met the food needs of the village, but, within the assessment process, identified other needs as well. This interdisciplinary approach facilitated holistic assessment of food, finances, personal self-worth and health.